Glass Ceiling in the Workplace: An Analysis within the Stated-owned Enterprises and Multi-national Enterprises in China - Cao, Mengxi (2015)
Currently, although the increasingly number of women has gained leadership positions, the glass ceiling phenomenon still exists in China, especially in multi-national enterprise. In brief, the road to the upper rungs for female is still challenging and difficult. Due to the nature of the enterprises, the performance of glass ceiling is different. The aim of this dissertation is to discuss different performance and influence of glass ceiling in the context of the multi-national enterprises (MNEs) and the stated-owned enterprises (SOEs). The extensive previous literatures examined general causes and reasons of glass ceiling in China whereas the research of comparison between multi-national enterprises and the stated-owned enterprises is limited. Therefore, this dissertation was based on two research questions including (1) how do MNEs and SOEs use organizational theories to achieve gender equality in the workplace; (2) how should women overcome the cognitive obstacles and challenge the traditional cultures and concepts to achieve a further progression in the workplace. This dissertation aims to answer such research questions through in-depth semi-structured interviews and all participants are from two different SOEs and MNEs of hotel industry respectively. In attempt to investigate the factors causing women slow down in their career advancement. It is discovered that the nature of enterprise has an impact on women’s promotion. Glass ceiling in MNEs is more evident and in SOEs gender equality can be nearly achieved. Further, women’s subjective aspiration also affects their mobility to top management. From the viewpoint of enterprises, building positive organizational culture, strengthening training system and mentoring programs and develop women-specific personnel policy will support women better planning their career.